Expression of collagenases matrix metalloproteinases and YB-1 oncogenic factor in malignant melanoma cancer cells and its regulation by stromal fibroblasts - Ibrahim, Wisam Nabeel; Abdul Wahab, Ridhwan; Abdull Rasad, Mohammad Syaiful Bahari (Asian Network of Scienctific Information, 2017)
Background and Objective: Fibroblast stromal cells actively participates in tumor invasion by secreting matrix metalloproteinases (MMPs) within the tumor microenvironment. Expression of these enzymes is primarily regulated at a transcriptional level via interaction with transcription factors. Among these factors, YB-1 oncogenic factor binds with different nucleic acids to exert its diverse influences. Also it represents an important prognostic indicator in many types of tumors. The aim of this study was to assess the expression of collagenases MMPs (MMP1, MMP8, MMP13) and the cellular proliferation in one of the most invasive types of cancer cell types which is the A375 malignant melanoma cancer cell line using co-culture settings. Also, the study attempted to assess the expression of YB-1 factor and its in vivo interaction with the AP-1 gene promoter sequence. Materials and Methods: The experiment involved growing A375 cells with CCD1079SK fibroblasts cells in co-culture environment. The proliferation of cells was determined using serial trypan blue assays, while the expression of YB-1, MMP1, MMP8 and MMP13 was determined by the use of real-time PCR and western blotting analysis. The potential interaction between YB-1 protein and AP-1 promoter sequence was assessed through chromatin immunoprecipitation (ChIP) assay. SPSS with independent t- test was used to compare cell proliferation and real-time PCR Ct mean values between samples. Results: In co-culture setting, the proliferation of A375 cancer cells was significantly faster than the cells in monoculture setting (5.1×105, 3×105 respectively in day 3) (p<0.05). Also, there was a significant increase in the expression of MMP1 enzyme. YB-1 and MMP8 were significantly expressed more in the A375 cancer cells in comparison with normal fibroblasts cells (p<0.05). Conclusion: The study confirms the role of stromal fibroblasts by enhancing the proliferation of melanoma cancer cells in vitro and increasing the expression of the MMP1 enzyme. In addition, YB-1 factor remains as an important prognostic indicator in cancer that might regulate expression of MMPs without binding to the AP-1 promoter sequence.